Os gestos vocais de Johnny Alf e Nat King Cole: uma análise comparativa - Rafael Augusto de Lima Barbosa (2023)
This research analyzes the vocal gestures (PICCOLO, 2006) present in the performances of Johnny Alf and Nat King Cole, aiming to compare the gestures of singers with similar musical characteristics. It compares interpretations of the same song, and by the same singer, at different moments of his career to understand similarities and diferences in vocal behavior. The methodology of analysis was divided in three parts: listening as the main analytical agent; the analysis of musical elements through partial transcription in score format; and the analysis of spectrograms as a visual and profound resource for the acoustic understanding of sound phenomena. This resource was called Multifaceted Vocal Analysis (MVA). In addition, the vocal gestures are schematically arranged here based on studies of hierarchical-musical organizations (LERDAHL; JACKENDOFF, 1983; SAVAGE et al., 2012; TENZER, 2006) and fed by the section on levels of vocal behavior proposed by Machado (2017;2012).